Using a Multi‐Attribute Decision‐Making Method to Evaluate the Effect of in Ovo Injection of Valine and Tryptophan on the Growth Performance of Broiler Chickens - Marziyeh Ebrahimi; Hoda Javaheri Barfourooshi; Seyed Abdullah Hosseini; Amir Hossein Alizadeh‐Ghamsari (Veterinary Medicine and Science)
ABSTRACT Background Eggs provide limited energy and essential nutrients necessary for chicken embryo growth. Intra‐egg nutrition serves as an effective approach to address initial growth constraints during the embryonic stage and post‐hatching. Objective This study aimed to identify the optimal levels of L‐valine or L‐tryptophan amino acids administered via in ovo injection to improve the growth performance of Ross 308 broiler chickens. Methods Five hundred fertile eggs were weighed and incubated. On Day 14, the fertile eggs were divided into five groups, receiving injections of either 0.95% (Val‐1) or 1.05% (Val‐2) L‐valine, 0.55% (Trp‐1) or 0.60% (Trp‐2) L‐tryptophan, or distilled water (control) at a volume of 0.5 mL. Nine performance criteria, including hatchability, body weight, feed intake, feed efficiency, livability, production index, villus length to crypt depth, Lactobacillus and Escherichia coli populations were assessed as least‐square means. Results A multiple‐attribute decision‐making (MADM) method, utilising the technique for order of preference similarity to the ideal solution (TOPSIS), was employed to rank the in ovo amino acid treatments. The treatments yielded the following scores: control (0.7703), Val‐1 (0.4759), Val‐2 (0.4161), Trp‐1 (0.7761) and Trp‐2(0.1509). Conclusions The findings indicate that injecting 0.55% L‐tryptophan on Day 14 of incubation is a beneficial strategy to enhance growth performance in broiler chickens.